Informational Description of Systemic Crises - A.V, Yudenkov; S.E., Terentyev; A.E, Kovaleva (International Journal of Engineering and Technology, 2018)
The paper studies the possibility of determining and classifying the crisis as a complex system by a remote observer on the basis of subjective information. Description and analysis of complex systems is a fundamentally unsolvable problem. However, there may be a partial solution to the problem through the use of multilevel modeling. Therefore, the development of new fairly common methods for modeling complex systems is an urgent task. The aim of the work is to develop fairly common methods of modeling complex systems in crisis. For this purpose, the evolution of the system is considered at three levels: micro level, meso level and macro level. At the micro level such concepts as unit of information, growth of information are considered. At the macro level, two models describing system crises are proposed. The simulation is based on stochastic differential equations and the theory of phase transitions. At the micro level, the process of transition from one stable state to another is studied. It is assumed that the remote macroscopic observer receives information about the evolution of the system. The new results include the following. A new interpretation of information from the quantum-statistical point of view. Unlike Shannonâ€™s information in this paper, the information is associated with the phase space of the system. This makes it possible to apply basic physical and mathematical methods to the study of the evolution of different nature of systems. An analogue of the second principle of thermodynamics at the micro level-the principle of maximum information is obtained. The obtained results allowed justifying the use of Langevin equations for crisis modeling, as well as to obtain an analogy between the types of crises and phase transitions. The paper considers illustrating examples of complex systems in the process of transition from one stable state to another.Â